Answer:
D
Step-by-step explanation:
To find the inverse, all we have to do is switch the x and f(x) so instead of f(x) = 5x + 6, it becomes:
x = 5f(x) + 6
x - 6 = 5f(x)
f⁻¹(x) = (x - 6) / 5
Answer:
coefficient of x: 2
coefficient of y: 3
coefficient of z: -7
Step-by-step explanation:
To solve this problem, first we need to sum the polynomials A and B, then we need to check the coefficients of x, y and z.
The sum of the polynomials is:
A + B = 5z + 4x^2 - 6y + 2 + 2x + 9y - 12z - 2
A + B = 4x^2 + 2x + 3y - 7z
So, the coefficients are:
coefficient of x^2: 4
coefficient of x: 2
coefficient of y: 3
coefficient of z: -7
The factors of 32 is 1,2,4,8,16, and 32.